2022
DOI: 10.3390/ijerph191811682
|View full text |Cite
|
Sign up to set email alerts
|

The Degree of Meeting the Needs of Older People with Frailty Syndrome in the Residential Environment in Relation to Interventions—Experimental Study

Abstract: The study aimed to determine the degree of satisfaction with health, psychological, environmental, and social needs and to determine the effects of a nutritional intervention, physical activity, and comprehensive activity (nutritional intervention plus physical activity) on the degree of satisfaction of the needs of older people with frailty syndrome (FS). The study included 188 residents (140 women and 48 men) and was conducted using the Fried scale and Camberwell’s modified brief needs assessment. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Physical activity is one of the indicators of active elderly that contributes to the slowing down of the frailty process in the elderly [25][26] . Several studies have shown that regular physical activity ranging from low-intensity walking, vigorous exercise, and resistance training has been shown to be safe for healthy and frail older people [26][27][28] .. Physical activity reduces the risk of major cardiovascular and metabolic diseases, obesity, falls, cognitive impairment, osteoporosis, and muscle weakness [29][30] .…”
Section: Resultsmentioning
confidence: 99%
“…Physical activity is one of the indicators of active elderly that contributes to the slowing down of the frailty process in the elderly [25][26] . Several studies have shown that regular physical activity ranging from low-intensity walking, vigorous exercise, and resistance training has been shown to be safe for healthy and frail older people [26][27][28] .. Physical activity reduces the risk of major cardiovascular and metabolic diseases, obesity, falls, cognitive impairment, osteoporosis, and muscle weakness [29][30] .…”
Section: Resultsmentioning
confidence: 99%
“…Understanding the intricate relationship between frailty and cognitive decline not only provides valuable prognostic insights but also opens avenues for targeted interventions. Interventions aimed at mitigating frailty, such as personalized exercise programs and nutritional interventions, have shown promise in preserving cognitive function and slowing down the progression of cognitive decline in frail individuals [49,50]. In addition, today's developments pave the way for non-invasive neuromodulatory treatments capable of enhancing brain reserve or mitigating potential pathological outcomes through neuromodulation interventions.…”
Section: Relevance Of Frailty As a Critical Markermentioning
confidence: 99%